First record of the family Coralliidae (Cnidaria: Anthozoa: Octocorallia) from the western South Atlantic, with a description of Corallium medea Bayer, 1964 - Castro, Clovis B.; Thiago, Cristovam M.; Medeiros, Marcelo S. (Zootaxa, 2003)
Specimens of precious coral obtained on oceanic seamounts off Brazil, at depths between 380 and 500 m, constitute the first record of the family Coralliidae in the South Atlantic. Colonies were identified as Corallium medea Bayer, 1964. One specimen was found associated with the deepwater reef forming scleractinian coral Lophelia pertusa (Linnaeus, 1758). In the Straits of Florida, C. medea is a quite common species in deep-water coral banks, which are partly dominated by L. pertusa. It is suggested that it will be found in deep coral reefs where L. pertusa has been recorded, 300 km from the oceanic bank where it was found in Brazil,